Protection Of Geographical Indications Of Andaliman Humbang Hasundutan Spices Is Reviewed From Law No. 20 Of 2016 Concerning Brands And Geographical Indications - Letare Sasja Natama; Miranda Risang Ayu; Helitha Novianty Muchta (Jurnal Indonesia Sosial Teknologi, 2023)
Indonesia is a country that has known for the richness of spices, one of which is andaliman. Andaliman is a spice that similar with pepper but has a bitter, spicy taste and distinctive aroma. Andaliman itself only grows in several districts in North Sumatra, one of which is Humbang Hasundutan District. Andaliman Humbang Hasundutan Regency has great potential in both national and international markets, and it can be said that andaliman is an Intellectual Property owned by Humbang Hasundutan Regency and Indonesia which must be given legal protection, namely Geographical Indications, but until now there has been no legal protection given to Andaliman Humbang Hasundutan. So the aim of this research is to see whether Geographical Indication protection can be given to Andaliman Humbang Hasundutan Regency based on Law no. 20 of 2016 concerning Brands and Geographical Indications. This research was conducted using qualitative research methods with a normative juridical approach. The results of this research are that Andaliman Humbang Hasundutan can be given Geographical Indication protection, however there are several elements that must be improved and fulfilled so that Andaliman Humbang Hasundutan and legal action that can be taken by the Government and the people of Humbang Hasundutan Regency are to fulfill the elements of Geographical Indication that has not been fulfilled by Andaliman Humbang Hasundutan.